Effort or ease: the impact of sharing self-improvement vs. hedonic behaviors on personal brand evaluation - Ruan, Chenhan; Zhang, Xiaoyang; Zhuo, Fenglian; Lu, Zhihuang; Li, Juan (Frontiers in Psychology, 2025)
Daily activities, as ubiquitous and relatable aspects of human life, have become a pivotal resource for social media influencers to build personal brands, with two primary types identified: hedonic behaviors (e.g., eating dessert) that pursue immediate sensory pleasure and emotional wellbeing, and self-improvement behaviors (e.g., learning) that focus on personal development for eudaimonic wellbeing. While previous studies mainly examined factors influencing consumers’ preferences between these two options, few have explored how such posts serve as signaling cues to shape consumer inferences. Drawing on Social Identity Theory, this study thus aims to investigate the impact of sharing hedonic versus self-improvement posts on personal brand evaluation. Employing four experiments, we tested our hypotheses across different samples and scenarios. The results show that self-improvement (vs. hedonic) posts elicit more positive inferences about sharers’ intrinsic motivation (Study 1), which in turn promotes personal brand evaluation (Studies 2–4). Moreover, two boundary conditions moderate this positive effect: it is attenuated in contexts with low social mobility (Study 3) or among viewers who perceive high similarity with the bloggers (Study 4). Overall, the findings enrich the theoretical understanding of social identification in posted activities, and provide practical implications for personal brand promotion.